Empowerment, transparency, technological readiness and their influence on financial performance, from a Latin American perspective : a sector study - Manríquez, Martha Ríos (Emerald Publishing Limited, 2021)
In a global economic crisis, many companies go out of business and millions of people are unemployed leaving businesses requiring new models that allow them to redefine themselves. Empowerment, Transparency, Technological Readiness and their Influence on Financial Performance, from a Latin American Perspective like Mexico, presents three key approaches that impact on company financial performance: Empowerment as a necessary approach for human capital to participate in company future. For this, significance, competency, self-determination, impact, and fluidity in the exchange of information, variables are considered Recovering values that have been tarnished by corruption at all levels, and improving transparency in companies through mechanisms as prevention, communication channels, and strategic alliances. The critical use of information and communication technologies as a means to offer products and services, avoiding bankruptcy. Analyzing the use of basic network services and the integration of ICT to improve business management and development, through sector analysis, studying the behavior of companies located in the state of Guanajuato for being one of the main states with the greatest economic dynamism in Mexico, but also one hardest hit by insecurity and corruption. Empowerment, Transparency, Technological Readiness and their Influence on Financial Performance, from a Latin American Perspective showcases in-depth analysis by size, sector of economic activity and type of ownership, allowing companies to obtain information for a broader vision to help make decisions about intervention, market performance and strategy development possibilities.